Search for the Standard Model Higgs boson produced in association with top quarks and decaying into [Formula: see text] in [Formula: see text] collisions at [Formula: see text] with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2015)
A search for the Standard Model Higgs boson produced in association with a top-quark pair, [Formula: see text], is presented. The analysis uses 20.3 fb-1 of pp collision data at [Formula: see text], collected with the ATLAS detector at the Large Hadron Collider during 2012. The search is designed for the [Formula: see text] decay mode and uses events containing one or two electrons or muons. In order to improve the sensitivity of the search, events are categorised according to their jet and b-tagged jet multiplicities. A neural network is used to discriminate between signal and background events, the latter being dominated by [Formula: see text]+jets production. In the single-lepton channel, variables calculated using a matrix element method are included as inputs to the neural network to improve discrimination of the irreducible [Formula: see text] background. No significant excess of events above the background expectation is found and an observed (expected) limit of 3.4 (2.2) times the Standard Model cross section is obtained at 95 % confidence level. The ratio of the measured [Formula: see text] signal cross section to the Standard Model expectation is found to be [Formula: see text] assuming a Higgs boson mass of 125[Formula: see text].